2015
DOI: 10.1038/ejhg.2015.28
|View full text |Cite
|
Sign up to set email alerts
|

Validation of rs2956540:G>C and rs3735520:G>A association with keratoconus in a population of European descent

Abstract: Corneal ectasias, among which keratoconus (KC) is the single most common entity, are one of the most frequent reasons for corneal grafting in developed countries and a threatening complication of laser in situ keratomileusis. Genome-wide association studies have previously found lysyl oxidase (LOX) and hepatocyte growth factor (HGF) associated with susceptibility to KC development. The aim of our study was to validate the effects of seven single-nucleotide polymorphisms (SNPs) within LOX and HGF over KC. Unrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
3

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 13 publications
1
24
1
3
Order By: Relevance
“…The finding that LOX was higher expressed in the high-response-to-CXL group compared to the low response group 51 further confirmed the function of LOX and its potential role in KC. However, some SNPs (rs2956540 [44][45][46] , rs10519694 46 , rs1800449 40,46 and rs2288393 46 ) confirmed in previous studies was undetected in this study, which may be due to the limited number of patients and different populations. Otherwise, a study in 2012 even did not find any pathogenic variant in KC 38 , and another gene expression microarray study showed a oppositely increasing trend in the KC patients compared to the normal controls 52 .…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The finding that LOX was higher expressed in the high-response-to-CXL group compared to the low response group 51 further confirmed the function of LOX and its potential role in KC. However, some SNPs (rs2956540 [44][45][46] , rs10519694 46 , rs1800449 40,46 and rs2288393 46 ) confirmed in previous studies was undetected in this study, which may be due to the limited number of patients and different populations. Otherwise, a study in 2012 even did not find any pathogenic variant in KC 38 , and another gene expression microarray study showed a oppositely increasing trend in the KC patients compared to the normal controls 52 .…”
Section: Discussioncontrasting
confidence: 55%
“…The LOX gene encodes a copper-dependent amine oxidase which is crucial for cross-linking of ECM, the stability of which is thus guaranteed 39 . Recently, more and more studies have shown LOX as a candidate gene for KC [38][39][40][41][42][43][44][45][46] . Multiple LOX mutations have been detected in sporadic (rs1800449 in the Iranian population 40 , rs2956540 in the Chinese 44 and European 45 population) and familial (rs2956540, rs10519694 rs1800449 and rs2288393 in the American population 46 ) cases.…”
Section: Discussionmentioning
confidence: 99%
“…The link between HGF variants and KC susceptibility was first reported by Burdon et al, (2011) and then confirmed in an independent European cohort which replicated the association of SNP rs3735520 and detected a new HGF SNP rs2956540 [ 34 ]. In addition, an independent study of an Australian population of European descent ( n = 830) focused on the HGF locus and detected a different SNP (rs4954218) significantly associated with KC [ 35 ].…”
Section: Resultsmentioning
confidence: 73%
“…Previous studies showed an independent, repeatable association between certain SNPs and HGF in KC [ 13 , 34 , 35 ]. The SNP variations detected were located in the noncoding region of HGF consistent with a role for these SNPs in the regulating HGF expression, and increased serum HGF expression associated with the minor SNP allele has been reported [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of Australian white study subjects with 933 keratoconus patients and more than 4000 controls, keratoconus susceptibility was detected at the HGF locus [82]. The risk factor allele rs3735520 was associated with keratoconus in a Czech cohort of 165 patients and 193 controls [83] and Australian whites of 157 patients and 673 controls [84]. Another study involved two independent cohorts of keratoconus patients, involving 222 Caucasian patients, 687 African Americans, 3324 Caucasian controls and 307 individuals from 70 keratoconus families reported strong association of Lysyl Oxidase gene (LOX) polymorphisms with keratoconus, with meta P-values of 2.5 × 10 −7 and 4.0 × 10 −5 for LOX SNPs rs2956540 and rs10519694 respectively [85].…”
Section: Central Corneal Thickness (Cct)mentioning
confidence: 99%